Regional Crustal and Lithospheric Thickness Model for Alaska, the Chukchi Shelf, and the Inner and Outer Bering Shelves - Torné, Montserrat; Jimenez-Munt, Ivone; Vergés, Jaume; Fernandez, Manel; Carballo, A.; Jadamec, M. (2020)
AGU Fall Meeting 2020 - online , 1 to 17 of December 2020 We present an integrated image of the lithosphere of Alaska and its western Chukchi and Bering seas shelves based on joint modeling of potential field data constrained by thermal analysis and seismic data. We also perform 3D forward modelling and inversion of Bouguer anomalies to analyze crustal density heterogeneities. The obtained crustal model shows NW regional thickening (32 to 36 km), with localized trends of thicker crust in the Brooks Range (40 km) and in the Alaska and St. Elias ranges (50 km). Offshore, 28¿30 km thick crust is obtained near the Bearing slope break and 36¿38 km in the northern Chukchi Shelf. In interior Alaska, the crustal thickness changes abruptly across the Denali fault, from 34-36 to the N to above 30 km to the S, that agrees with the presence of a crustal tectonic buttress guiding block motion W and S to the subduction zone. The average crustal density is 2810 kg¿m-3. Denser crust (2910 kg¿m-3) is found S of the Denali Fault related to the oceanic nature of the Wrangellia Composite Terrane rocks. Offshore, less dense crust (< 2800 kg¿m-3) is found along the basins of the Chukchi and Beaufort shelves. At LAB levels, there is a regional SE¿NW trend that coincides with the Pacific plate motion, with a lithospheric root beneath the Brooks Range, Northern Slope, and Chuckchi Sea, that may be a relic of the Chukotka-Artic Alaska microplate. The lithospheric root (> 180 km) agrees with the presence of a boundary of cold, strong lithosphere that deflects the strain to the south. South of the Denali Fault the LAB topography is quite complex. East of 150 °W, below Wrangellia and the eastern side of Chugach terranes, the LAB is much shallower than it is west of this meridian. The NW trending limit separating thinner lithosphere in the East and thicker in the West agrees with the two¿tiered slab shape of the subducting Pacific Plate. This research has been funded by the We¿Me project (PIE¿CSIC¿201330E111), AGUR 2017¿SGR¿847, ...